First-principle Investigations on Electronic and Optical Properties of LiZnAs under Pressure up to 20 GPa - Liang, Hailong; An, Hongen; Liew, Willey Yun Hsien; Ismal Saad; Bih, Lii Chua; Nancy Julius Siambun; Liu, Lu; Qu, Shuwei; Li, Ruiqin; Yao, Wei (Springer, 2025)
Density functional theory (DFT) studies were performed on the lattice parameters, electronic band structure, and optical constants under pressure up to 20 GPa in order to obtain insight into the electronic and optical properties of LiZnAs. The calculated results show LiZnAs is a semiconductor with a direct gap of 0.86 eV, which is smaller than the experimental value 1.1 eV. It also indicates that the structural parameters such as lattice parameters and cell volume show inverse relation to the pressure and shows smooth decreasing behavior from 0 to 20 GPa. Meanwhile, the pressure dependence of the electronic band structure, density of states and partial density of states of LiZnAs up to 20 GPa were presented. And we found that the band gap increased with the pressure. Moreover, the evolution of the dielectric function, absorption coefficient α(ω), reflectivity R(ω), the refractive index n(ω), and the extinction coefficient k(ω) of LiZnAs under pressure were presented. According to our work, we found that the optical properties of LiZnAs undergo a blue shift with increasing pressure. These results suggest technological applications of such materials in extreme environments.